The Yorkshire Dales : The North and East: The Howgill Fells, Mallerstang, Swaledale, Wensleydale, Coverdale and Nidderdale /: The North and East: The Howgill Fells, Mallerstang, Swaledale, Wensleydale, Coverdale and Nidderdale. (2015) - Kelsall, Dennis; Kelsall, Jan
No abstract available